Overtreatment as an ethical dilemma in Australian private dentistry: A qualitative exploration. Issue 2 (1st November 2020) - Holden, Alexander C. L.; Adam, Lee; Thomson, W. Murray
Abstract: Background: The phenomenon of overtreatment in dentistry is under‐explored and has not been the subject of much research inquiry. Most dental care in Australia is provided by practitioners in private dental practice. This research expands understanding of how the nexus between professionalism and commercialism in dentistry is impacted by the phenomenon of overtreatment. Methods: Data were collected through recorded interviews and written reflections from private dentists working in the Australian context. The data were then examined using thematic analysis to understand common themes and reveal deeper insights. Results: A total of 20 participants were recruited for this study. Participants spoke of their experiences in practice where financial targets and pressure from practice owners to provide high‐cost treatments presented challenges to their professionalism. The participants expressed that the way in which dentistry is remunerated based on activity was a motivation towards engaging in overtreatment. The participants also spoke of finding a balance between commercialism and professionalism within private dental practice. Conclusions: Participants' reports provided insights into how the mismanagement of the commercial elements of private dental practice led to a transactional ('buyer beware') relationship between the consumers and providers of dental services, rather than a relationship founded upon professional altruism and trust. Consumer empowerment through the commercialization of dentistry has potential to be a positive influence on the patient experience in accessing dental care. However, this research has shown that the shift of power through consumerism also risks attenuating professional appreciation of the imbalanced nature of the patient‐clinician relationship in dentistry.